Preparation method of copper-plated titanium alloy wire reinforced aluminum-based composite material
The method of preparing aluminum matrix composites reinforced with copper-plated titanium alloy wire has solved the problem of poor interfacial properties and improved the strength and ductility of aluminum matrix composites.
Patent Information
- Application Number
- CN202410706332.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-06-03
AI Technical Summary
Existing titanium fiber reinforced aluminum matrix composites have poor interfacial properties, which limits their mechanical properties.
A method for preparing copper-plated titanium alloy wire reinforced aluminum matrix composites is adopted, including TC4 wire pretreatment, copper plating, and two-step slow thermal treatment. Combined with arc additive manufacturing technology, a bond is formed between the copper-plated titanium alloy wire and the aluminum matrix composite.
It improves the bonding strength of the aluminum-titanium interface, inhibits the formation of brittle intermetallic compounds, and enhances the strength and ductility of aluminum-based composite materials.
Smart Images

Figure CN118699394B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-based composite materials and relates to a preparation method of a copper-plated titanium alloy wire reinforced aluminum-based composite material. Background Art
[0002] Aluminum-based composites have the advantages of high strength, low density, high damping and high wear resistance, and have broad application prospects in the automotive industry and aerospace. Aluminum-based composites based on 5xxx series aluminum alloys have excellent corrosion resistance and weldability, but their tensile strength is not as good as that of aluminum-based composites based on 2xxx series and 7xxx series aluminum alloys, which limits their application under high load conditions. Heat treatment is usually used to improve the mechanical strength of materials, but in practical applications, aluminum-based composites based on 5 series aluminum alloys are difficult to strengthen by heat treatment, because heat treatment causes a sharp drop in the elongation of the material, thereby affecting the overall mechanical properties of the material. At present, the methods for improving the mechanical properties of aluminum-based composites mainly include adding continuous reinforcements and discontinuous reinforcements. Fiber-reinforced aluminum-based composites in continuous reinforcements and short-fiber-reinforced aluminum-based composites in discontinuous reinforcements can only prepare simple parts. Although whiskers, particles, and nanoparticles / nanotubes reinforced aluminum-based composites in discontinuous reinforcements can improve the hardness and strength of aluminum-based composites, their plasticity and toughness are significantly reduced. Therefore, it is necessary to find new methods to improve strength and ductility at the same time. Titanium alloy wire has the advantages of high strength, good thermal stability and corrosion resistance, and has similar elongation to aluminum alloy. Therefore, embedding titanium alloy wire as continuous fiber into aluminum-based composites to improve the mechanical properties of composites has important application prospects.
[0003] Based on the directed energy deposition additive manufacturing technology, the team of Academician Lu Bingheng and Associate Professor Fang Xuewei of Xi'an Jiaotong University invented a new additive manufacturing technology for metal continuous fiber reinforced composite materials, realizing the manufacturing of titanium fiber reinforced aluminum (TFRA) components for the first time, and the comprehensive mechanical properties were greatly improved (Yongliang G, Meng Z, XinZhi L, et al. Wire-based directed energy deposition of a novel high-performance titanium fiber-reinforced Al5183 Aluminum Alloy [J]. Additive Manufacturing, 2023, 65). Chinese patent CN106319400A discloses a high-damping nickel-titanium wire reinforced aluminum-based composite material and its preparation method. The reinforcing phase of the aluminum-based composite material is a nickel-titanium alloy wire that is hot-rolled after casting. The nickel-titanium wire reinforced aluminum-based composite material prepared by this method has excellent damping performance and mechanical properties. However, due to the large differences in the physical and chemical properties of aluminum and titanium, the metallurgical reactions in the existing methods are very likely to generate brittle intermetallic compounds such as Ti3Al, TiAl, TiAl3, Ti2Al5, etc., resulting in poor interface performance of the manufactured titanium fiber reinforced aluminum-based composites. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material, which solves the problem of poor interface performance of the existing titanium fiber reinforced aluminum-based composite material.
[0005] The technical solution adopted by the present invention is a method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material, comprising the following steps:
[0006] Step 1, TC4 wire pretreatment, including etching and activating the cleaned TC4 wire;
[0007] Step 2, electroplating a copper layer on the TC4 wire after etching and activation treatment to obtain a copper-plated titanium alloy wire;
[0008] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including first raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes, then raising the temperature to 820-880°C at 10°C / min and keeping it for 15min-60min, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 820-880°C to 740°C and keeping it for 5min, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0009] Step 4: Use arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer.
[0010] Among them, the diameter of the TC4 wire is 0.2mm-0.5mm, and the thickness of the copper coating of the copper-plated titanium alloy wire is 50μm-80μm.
[0011] In step 1, the TC4 wire is pretreated, including first sanding the surface of the TC4 wire, then acid washing with H2SO4, alkaline washing with NaOH to remove oil, and then cleaning with alcohol. After cleaning, it is dried and finally etched and activated. The H2SO4 concentration used is 5-10wt%, and the NaOH concentration is 1-3wt%.
[0012] In step 1, the cleaned TC4 wire is etched and activated with an etching solution, the etching temperature is 35-50°C, the etching time is 15min-30min, and the etching solution is composed of 10-15wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 5-10wt% H2O. The total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0013] In step 2, the TC4 wire after etching and activation treatment is electroplated with a copper layer, the deposition temperature is 60-80° C., the deposition current is 0.01-0.09A, and the deposition time is 30min-120min.
[0014] In step 2, the TC4 wire after etching and activation treatment is electroplated with a copper layer, and the electroplating solution composition is 55-83wt% CuSO4·5H2O, 14-42wt% H2SO4, ≤1wt% emulsifier, ≤1wt% sodium sulfonate and ≤1wt% sodium chloride, and the total mass percentage of the above components is 100%.
[0015] In step 4, arc additive manufacturing technology is used to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate. The raw material used is ER5356 aluminum alloy wire, the wire feeding speed is 600 mm / min, the current is 60-100 A, and the pure argon shielding gas flow rate is 15 L / min.
[0016] In step 4, the process for depositing a single layer and single pass of ER5356 aluminum alloy substrate on the surface of the intermediate layer is the same as the process for depositing a single layer and single pass of ER5356 aluminum alloy on the aluminum alloy substrate.
[0017] The beneficial effects of the present invention are as follows:
[0018] (1) Using copper as the transition interlayer at the aluminum-titanium interface can effectively inhibit the formation of brittle intermetallic compounds between aluminum and titanium, thereby improving the interface performance and making the aluminum-titanium interface have higher strength;
[0019] (2) The TC4 wire is subjected to etching activation treatment and then electroplated with a copper layer, and finally a heat treatment furnace is used to perform a two-step slow cooling and heating treatment on the copper-plated titanium alloy wire, which can effectively improve the bonding strength between titanium and copper. The traditional heat treatment process has a fast cooling speed, which causes severe shrinkage of the copper base material and easily leads to crack defects at the interface between the copper base material and the intermetallic compound. The present application sets the cooling process to two steps, which can slow down the shrinkage of the copper-plated titanium alloy wire and release residual stress, thereby avoiding the formation of microcracks at the titanium-copper interface.
[0020] (4) The copper-plated titanium alloy wire is embedded into the aluminum-based composite material using arc additive manufacturing technology. The copper-plated titanium alloy wire can hinder the thermal expansion and contraction behavior between the metal bonding layers and evenly distribute the force to each metal wire, thereby improving the strength and elongation of the aluminum-based composite material;
[0021] (5) Under the action of copper-plated titanium alloy wire, the flexural strength of the aluminum-based composite material is 805-917 MPa, which is 21%-37% higher than that of the aluminum matrix, and the impact energy is 47-65 J, which is 95%-170% higher than that of the aluminum matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of performing two-step slow cooling and heating treatment on the copper-plated titanium alloy wire in the preparation method of the copper-plated titanium alloy wire reinforced aluminum-based composite material of the present invention;
[0023] Figure 2 Schematic diagram of the microstructure of the copper-plated titanium alloy wire in Example 1 of the present invention;
[0024] Figure 3 is a scanning energy spectrum diagram of a cross section of a copper-plated titanium alloy wire in Example 1 of the present invention;
[0025] Figure 4 is a SEM image of the copper-plated titanium alloy wire reinforced aluminum-based composite material in Example 1 of the present invention;
[0026] Figure 5 This is a SEM image of the copper-plated titanium alloy wire reinforced aluminum-based composite material in Comparative Example 1 of the present invention.
[0027] In the figure, 1. TC4 wire, 2. copper plating, 3. ER5356 aluminum alloy substrate. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] The preparation method of the copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0030] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.2mm-0.5mm, then performing H2SO4 pickling in a concentration of 5-10wt% H2SO4, alkali washing and degreasing in a concentration of 1-3wt% NaOH, then cleaning with alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 35-50°C, the etching time is 15min-30min, the etching solution is composed of 10-15wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 5-10wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0031] Step 2, electroplating a copper layer on the TC4 wire 1 after etching activation treatment, the electroplating solution composition is 55-83wt% CuSO4·5H2O, 14-42wt% H2SO4, ≤1wt% emulsifier, ≤1wt% sodium sulfonate and ≤1wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature during the electroplating copper layer is 60-80°C, the deposition current is 0.01-0.09A, and the deposition time is 30min-120min to obtain a copper-plated titanium alloy wire, and the copper plating layer 2 of the copper-plated titanium alloy wire has a thickness of 50μm-80μm;
[0032] Step 3, refer to Figure 1 , a heat treatment furnace is used to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including first raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes, then raising the temperature to 820-880°C at 10°C / min and keeping it for 15min-60min, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 820-880°C to 740°C and keeping it for 5min, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0033] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 60-100 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0034] Example 1
[0035] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0036] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.2mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 at a concentration of 5wt%, alkaline washing and degreasing in NaOH at a concentration of 2wt%, and then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 35°C, the etching time is 15min, the etching solution is composed of 10wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 10wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0037] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 55wt% CuSO4·5H2O, 42wt% H2SO4, 1wt% emulsifier, 1wt% sodium sulfonate and 1wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 60°C, the deposition current is 0.01A, and the deposition time is 120min, to obtain a copper-plated titanium alloy wire;
[0038] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 820°C at 10°C / min and keeping it for 30 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 820°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0039] The microstructure of the copper-plated titanium alloy wire after two-step slow cooling and heating treatment was observed, and its cross-sectional structure is as follows: Figure 2 As shown, the inside is TC4 wire 1 and the outside is copper-plated layer 2. The cross-section elements of the copper-plated titanium alloy wire are detected, and the outermost layer of the copper-plated titanium alloy wire is taken as the coordinate origin and gradually extended to the inside to obtain the scanning energy spectrum line diagram of the cross-section of the copper-plated titanium alloy wire, as shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that the Cu content of the copper-plated titanium alloy wire decreases gradually from the outside to the inside, while the Ti, Al and V contents increase gradually. Near the junction of the TC4 wire 1 and the copper plating 2, the Ti, Al and V contents increase sharply, while the Cu content decreases sharply, almost to 0, indicating that the copper plating 2 can hinder the contact between the aluminum alloy matrix and the TC4 wire 1, and effectively inhibit the formation of brittle intermetallic compounds between aluminum and titanium.
[0040] Step 4, use arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate. The raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 60 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy substrate 3 is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0041] Comparative Example 1
[0042] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0043] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.2mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 at a concentration of 5wt%, alkaline washing and degreasing in NaOH at a concentration of 2wt%, and then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 35°C, the etching time is 15min, the etching solution is composed of 10wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 10wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0044] Step 2, electroplating a copper layer on the TC4 wire 1 after etching activation treatment, the electroplating solution composition is 55wt% CuSO4·5H2O, 42wt% H2SO4, 1wt% emulsifier, 1wt% sodium sulfonate and 1wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 60°C, the deposition current is 0.01A, and the deposition time is 120min, to obtain a copper-plated titanium alloy wire;
[0045] Step 3, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 60 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the copper-plated titanium alloy wire is flatly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0046] Compared with Example 1, Comparative Example 1 lacks two steps of slow cooling and heating treatment, and other processes are the same.
[0047] The microstructure of the copper-plated titanium alloy wire reinforced aluminum-based composite material prepared in Example 1 and Comparative Example 1 was observed. The observation results are as follows: Figure 4 and Figure 5 As shown, it includes TC4 wire 1, copper plating 2 and ER5356 aluminum alloy matrix 3. It can be seen from the figure that the copper-plated titanium alloy wire reinforced aluminum-based composite material prepared in Example 1 has a good titanium-copper interface state without the generation of cracks. The copper-plated titanium alloy wire reinforced aluminum-based composite material prepared in Comparative Example 1 has obvious cracks between the titanium-copper interface without two-step slow cooling and heating treatment, indicating that the two-step slow cooling and heating treatment can slow down the shrinkage of the copper-plated titanium alloy wire and release residual stress, thereby avoiding the formation of microcracks at the titanium-copper interface.
[0048] Example 2
[0049] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0050] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.3mm with sandpaper, the sandpaper mesh number is 60 mesh, then H2SO4 pickling in a concentration of 6wt% H2SO4, alkaline washing and degreasing in a concentration of 1wt% NaOH, and then cleaning with a concentration of 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 40°C, the etching time is 20min, the etching solution is composed of 12wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 8wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0051] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 60wt% CuSO4·5H2O, 37wt% H2SO4, 1wt% emulsifier and 1wt% sodium sulfonate and 1wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 70°C, the deposition current is 0.03A, and the deposition time is 100min to obtain a copper-plated titanium alloy wire;
[0052] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 840°C at 10°C / min and keeping it for 30 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 840°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0053] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 70 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0054] Example 3
[0055] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0056] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.4mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 at a concentration of 7wt%, alkaline washing and degreasing in NaOH at a concentration of 1wt%, and then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 45°C, the etching time is 25min, the etching solution is composed of 13wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 7wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0057] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 65wt% CuSO4·5H2O, 33wt% H2SO4, 1wt% emulsifier and 0.5wt% sodium sulfonate and 0.5wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 70°C, the deposition current is 0.05A, and the deposition time is 90min, to obtain a copper-plated titanium alloy wire;
[0058] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 860°C at 10°C / min and keeping it for 30 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 860°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0059] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 80 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0060] Example 4
[0061] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0062] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.5mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 at a concentration of 7wt%, alkaline washing and degreasing in NaOH at a concentration of 3wt%, then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 45°C, the etching time is 25min, the etching solution is composed of 13wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 7wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0063] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 72wt% CuSO4·5H2O, 26wt% H2SO4, 1wt% emulsifier and 0.2wt% sodium sulfonate and 0.8wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 68°C, the deposition current is 0.06A, and the deposition time is 80min, to obtain a copper-plated titanium alloy wire;
[0064] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 880°C at 10°C / min and keeping it for 30 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 880°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0065] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 90 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0066] Example 5
[0067] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0068] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.5mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 at a concentration of 8wt%, alkaline washing and degreasing in NaOH at a concentration of 1wt%, then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 48°C, the etching time is 28min, the etching solution is composed of 15wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 5wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0069] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 78wt% CuSO4·5H2O, 20wt% H2SO4, <1wt% emulsifier and 0.4wt% sodium sulfonate and 0.6wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 70°C, the deposition current is 0.07A, and the deposition time is 70min, to obtain a copper-plated titanium alloy wire;
[0070] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 840°C at 10°C / min and keeping it for 15 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 840°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0071] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 100 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0072] Example 6
[0073] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0074] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.2mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 at a concentration of 9wt%, alkaline washing and degreasing in NaOH at a concentration of 2wt%, then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 50°C, the etching time is 30min, the etching solution is composed of 15wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 5wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0075] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 80wt% CuSO4·5H2O, 17wt% H2SO4, 1wt% emulsifier and 1wt% sodium sulfonate and 1wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 80°C, the deposition current is 0.08A, and the deposition time is 30min, to obtain a copper-plated titanium alloy wire;
[0076] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 840°C at 10°C / min and keeping it for 45 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 840°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0077] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 70 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0078] Example 7
[0079] A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material comprises the following steps:
[0080] Step 1, TC4 wire pretreatment, including first sanding the surface of the TC4 wire with a diameter of 0.4mm with sandpaper, the sandpaper mesh number is 60 mesh, then pickling with H2SO4 in a concentration of 10wt%, alkaline washing and degreasing in NaOH with a concentration of 3wt%, then cleaning with 95% alcohol, drying after cleaning, and finally etching activation treatment, the etching temperature is 50°C, the etching time is 30min, the etching solution is composed of 15wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 5wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%.
[0081] Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 83wt% CuSO4·5H2O, 15wt% H2SO4, 0.5wt% emulsifier and 1wt% sodium sulfonate and 0.5wt% sodium chloride, the total mass percentage of the above components is 100%, the deposition temperature is 80°C, the deposition current is 0.09A, and the deposition time is 40min, to obtain a copper-plated titanium alloy wire;
[0082] Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes to ensure that the contact surface of the sample is in close contact and eliminate microscopic gaps, then raising the temperature to 840°C at 10°C / min and keeping it for 60 minutes, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 840°C to 740°C and keeping it for 5 minutes, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace;
[0083] Step 4, using arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate, the raw material used is ER5356 aluminum alloy wire, the diameter of the ER5356 aluminum alloy wire is 1.2 mm, the wire feeding speed is 600 mm / min, the current is 80 A, and the pure argon shielding gas flow rate is 15 L / min. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer. The process used is the same as the process of single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate.
[0084] The mechanical properties of the ER5356 aluminum alloy matrix, the uncopper-plated TC4 wire (with a diameter of 0.2 mm) and the copper-plated titanium alloy wire reinforced aluminum matrix composite material prepared in Examples 1-7 were tested respectively. The test results are shown in Table 1:
[0085] Table 1 Mechanical properties of aluminum alloy substrate, uncoated copper TC4 wire and samples prepared in Examples 1-7
[0086]
[0087]
[0088] It can be seen from Table 1 that the copper-plated titanium alloy wire reinforced aluminum-based composite material prepared by the method of the present invention has good strength and ductility.
Claims
1. A method for preparing a copper-plated titanium alloy wire reinforced aluminum-based composite material, characterized in that: The following steps are involved: Step 1, TC4 wire pretreatment, including etching and activating the cleaned TC4 wire; In the step 1, the TC4 wire is pretreated, including first sanding the surface of the TC4 wire, then acid-washing with H2SO4 and alkaline-washing with NaOH to remove oil, the H2SO4 concentration used is 5-10wt%, and the NaOH concentration is 1-3wt%, then washing with alcohol, drying after washing, and finally etching and activation treatment; In the step 1, the cleaned TC4 wire is etched and activated with an etching solution, the etching temperature is 35-50°C, the etching time is 15min-30min, the etching solution is composed of 10-15wt% HF aqueous solution, 10wt% NH4HF2, 70wt% ethylene glycol and 5-10wt% H2O, the total mass percentage of the above components is 100%, and the volume concentration of the HF aqueous solution is 40%; Step 2, electroplating a copper layer on the TC4 wire after etching activation treatment, the electroplating solution composition is 55-83wt% CuSO4·5H2O, 14-42wt% H2SO4, ≤1wt% emulsifier, ≤1wt% sodium sulfonate and ≤1wt% sodium chloride, the total mass percentage of the above components is 100%; the deposition temperature is 60-80°C, the deposition current is 0.01-0.09A, and the deposition time is 30min-120min to obtain a copper-plated titanium alloy wire, the diameter of the TC4 wire is 0.2mm-0.5mm, and the copper plating thickness of the copper-plated titanium alloy wire is 50µm-80µm; Step 3, using a heat treatment furnace to perform a two-step slow cooling heat treatment on the copper-plated titanium alloy wire, including first raising the furnace temperature to 740°C at 10°C / min and keeping it for 10 minutes, then raising the temperature to 820-880°C at 10°C / min and keeping it for 15min-60min, and then performing two-stage slow cooling, the cooling rate of the two-stage slow cooling is 5°C / min, the first stage is cooling from 820-880°C to 740°C and keeping it for 5min, the second stage is cooling from 740°C to 500°C, and finally cooling to room temperature with the furnace; Step 4: Use arc additive manufacturing technology to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate. Subsequently, the heat-treated copper-plated titanium alloy wire is evenly laid in the center of the cladding layer to form an intermediate layer, and finally a single-layer single-pass ER5356 aluminum alloy matrix is clad on the surface of the intermediate layer.
2. The method for preparing the copper-plated titanium alloy wire reinforced aluminum-based composite material according to claim 1, characterized in that: In the step 4, arc additive manufacturing technology is used to perform single-layer single-pass cladding of ER5356 aluminum alloy on the aluminum alloy substrate. The raw material used is ER5356 aluminum alloy wire, the wire feeding speed is 600 mm / min, the current is 60-100 A, and the pure argon shielding gas flow rate is 15 L / min.
3. The method for preparing the copper-plated titanium alloy wire reinforced aluminum-based composite material according to claim 2, characterized in that: In step 4, the process of depositing a single layer and a single pass of ER5356 aluminum alloy substrate on the surface of the intermediate layer is the same as the process of depositing a single layer and a single pass of ER5356 aluminum alloy on the aluminum alloy substrate.
Citation Information
Patent Citations
High-damping aluminum matrix composite reinforced by Ni-Ti wire and preparing method thereof
CN106319400A
Manufacturing method of titanium fiber
CN114713658A
Plasma-arc in-situ welding technology of granular enhanced aluminum-based composite material
CN1895830A